2019
DOI: 10.1002/bse.2278
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of materiality disclosure quality in integrated reporting: Empirical evidence from an international setting

Abstract: This study examines determinants of materiality disclosure quality (MDQ) in integrated reporting (IR) in an international setting. To this purpose, we constructed a novel, hand-collected MDQ score in line with the guiding principles introduced by the International Integrated Reporting Council. On the basis of a cross-national sample consisting of 359 firm-year observations between 2013 and 2016, we find that MDQ is positively associated with learning effects, gender diversity, and the assurance of nonfina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(213 citation statements)
references
References 183 publications
(249 reference statements)
8
164
1
7
Order By: Relevance
“…These aspects imply that companies that provide for the presence of women on the board provide higher quality information within integrated reports, capable of reducing agency costs. With reference to board diversity, our findings are similar to those obtained by Prado‐Lorenzo and García‐Sánchez () and Barako and Brown () in reference to sustainability reporting, whereas, in the context of integrated reporting, they extend the results by Frias‐Aceituno et al (2013a), Gerwanski et al (), and Kilic and Kuzey ().…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These aspects imply that companies that provide for the presence of women on the board provide higher quality information within integrated reports, capable of reducing agency costs. With reference to board diversity, our findings are similar to those obtained by Prado‐Lorenzo and García‐Sánchez () and Barako and Brown () in reference to sustainability reporting, whereas, in the context of integrated reporting, they extend the results by Frias‐Aceituno et al (2013a), Gerwanski et al (), and Kilic and Kuzey ().…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, some researchers have extended the scope of these studies to integrated reporting. In this regard, some studies have analysed the impact of gender diversity (Alfiero, Cane, Doronzo, & Esposito, 2017;Fasan & Mio, 2017;Frias-Aceituno et al, 2013a;García-Sánchez & Noguera-Gámez, 2018;Gerwanski et al, 2019;Kilic & Kuzey, 2018), whereas others examined foreign diversity (Frias-Aceituno et al, 2013a) and age diversity (Alfiero et al, 2017). In relation to gender diversity, Frias-Aceituno et al (2013a) found that the presence of women on the board favours the adoption of integrated reporting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with this idea, several studies (Hodge, 2001;Hodge, Hopkins, & Pratt, 2006;Kelton, Pennington, & Tuttle, 2010;Koonce & Mercer, 2005) find that informationally equivalent disclosures that vary only in their ease of processing can have differential effects on market prices. Two of the most important IR principles (connectivity and materiality, discussed above) are precisely aimed at presenting information in a concise and holistic way (Gerwanski, Kordsachia, & Velte, 2019). One of the aims of the connectivity principle is to allow the understanding of the impact of different capital on the financial performance of the company.…”
Section: Financial Analysts and Irmentioning
confidence: 99%
“…Following Kim, Park, & Wier's (2012) evidence, Gerwanski, Kordsachia, & Velte (2019) argued that management teams are less likely to carry out earnings manipulation when firms impose better terms of materiality disclosure. However, their study does not provide statistically significant results.…”
Section: Em and Csrmentioning
confidence: 99%
“…However, their study does not provide statistically significant results. Gerwanski, Kordsachia, & Velte (2019) justify this evidence by highlighting that "possible explanations can be derived from the related topic on the association between CSR and earnings management" (Gerwanski, Kordsachia, & Velte, 2019, p. 14). Additionally, Hong and Andersen (2011) explored the relationship between CSR and EM using a sample of nonfinancial U.S. firms for 1995֪-2005 and while assuming that EM reduces the quality of financial reporting.…”
Section: Em and Csrmentioning
confidence: 99%